Geospatial modeling urban growth pattern in Siem Reap, Cambodia - Chanvoleak Ourng; Tripathi, Nitin Kumar; Taravudh Tipdecho; Kamiya, Yoshikazu; Japan Government (Pathum Thani : Asian Institute of Technology, 2011)
I would like t o expr ess great appreciation and sincere thanks to my advisor and chairperson of thesis committee for Master of Science in Remote Sensing and Ge o graphic Information, Dr. Nitin Kumar Tripathi for his guidance, constructive suggestions, criticisms, and encouragement during this research work. I also thank my thesis committee member, Dr. Taravudh Tipdecho for valuable advices and helping me to successfully complete my thesis. His willingness to give his time so generously has been very much appreciated. I would also like to extent my thank s to Dr. Yoshikazu Kamiya , thesis committee member for his comments and effective guidance. Sincere appreciation and thanks to Japan Government to provide me scholarship to study at Asian Institute of Technology, Tha iland and giving an opportunity of international research exposure. I would like to thanks to my dear friend, Mr. Akhtar Nawaz Khan for his guidance and encouragement to work hard during my stay at AIT, Thailand. Specia l thanks to my parents, auntie s, brother and other family members for their moral and spiritual support throughout my studies. Once again, I would like to pay special thanks to my beloved mother for her patience and big sacrifice to allow me to study abroad.
A thesis submitted in partial fulfillment of the requirement s for the degree of Master of Science in Remote Sensing and Geographic Information System, School of Engineering and Technology
Thesis (M. Sc.) - Asian Institute of Technology, 2011
Keywords: Cities and towns -- Growth -- Cambodia -- Siem Reap; Land use -- Cambodia -- Siem Reap